The Effectiveness of Utilizing Spoof Text in English Language Learning for Students of SMA Negeri 4 Praya - Wulandari, Aini Husnida; Sugianto, Riris (ISLAMIKA, 2024)
This study explores the efficacy of incorporating spoof texts into high school education, specifically focusing on enhancing students' knowledge and process skills. Employing a pre-post-test experimental design with control and experimental groups at SMA Negeri 4 Praya, students engaged with spoof material through diverse mediums such as learning videos, spoof images, and audio-visual texts. Utilizing student worksheets (LKS) to support comprehension, the results indicate that the integration of spoof texts effectively develops students' knowledge and skills. Students demonstrated the ability to explain spoof material from various sources, showing increased engagement during the learning process. The implementation of LKS further supported their understanding of spoof texts. These findings contribute significantly to high school learning methodologies, with practical implications for curriculum development and teaching strategies aimed at enhancing students' grasp of spoof texts. Future research may delve into additional aspects of spoof text utilization to deepen understanding of their impact on students' knowledge and process skills development.